STUDY OF VISUAL PERCEPTION IN PRIMARY SCHOOL STUDENTS IN THE ASPECT OF PREVENTION OF MYOPIA (EDUCATION IN THE 21ST CENTURY, 2023)
The article analyzes the results of studies on the formation and development of visual perception of visually impaired children in the aspect of correction and prevention of myopia, conducted by foreign and domestic authors. First of all, the urgency of the problem is determined by the fact that visual impairment significantly complicates the process of reading and writing in these children. Due to the insufficient development of visual perception, visually impaired students write letters, syllables or words together or excessively separately, violate the directness of writing, etc.      In the special scientific and methodological literature, much attention is paid to the formation and development of visual perception in children with visual impairments, research in this many foreign and domestic researchers are engaged in the field.      However, in the ongoing work, due attention is not paid to the development of visual perception of visually impaired children in the framework of the correction and prevention of myopia. Whereas the solution of this problem is very important for these children.      Therefore, the issue of studying the ways and means of creating and developing visual perception techniques, reading from flat surfaces, correcting the prevention of myopia in children with visual impairment is important for the theory and practice of teaching students in special, inclusive and general education schools.The above stated determines the relevance of this study, its theoretical and practical significance.
Keywords: children; students; teacher; parents; visual impairment; research; correction; prevention; visual perception; myopia; visually impaired children; optical-graphic impairment of writing